Boundaries of visual phenomena in migraine: the charles bonnet’s syndrome - report of two cases - Pelliciari, Davy Henrique Sousa; Bordini, Carlos Alberto (Headache Medicine, 2024)
IntroductionTwo patients were referred to a tertiary headache center due to complex visual phenomena that might be related to migraine aura. Eventually, it turned out that they were Charles Bonnet syndrome (CBS) patients. The syndrome is characterized by vivid visual hallucinations in the absence of other psychiatric symptoms, often in patients with optical morphophysiological disorders. The pathophysiology of CBS remains uncertain, and the syndrome lacks robust diagnostic criteria. So far, reports on CBS are scarce in Brazilian neurological literature, leading to challenges in identification and diagnosis. The condition is primarily recognized through anamnesis and clinical examination.ObjectiveTo report two cases of CBS to draw the attention of headache specialists about this syndrome.Case reportsThe first case involves a 93-year-old male patient, retired, who reported experiencing vivid hallucinations sometimes of an old white car and sometimes a group of children. Despite the clarity of these visions, the patient remained aware that they were not real. In the second case, a 70-year-old male farmer began experiencing hallucinations involving scratches, scribbles, letters, stones, and women in his visions. ConclusionHere two cases of CBS were reported concerning a not so rare condition, but for sure very uncommon to headache specialists.